Psychological contract breach and rumination about job insecurity: How and when crisis-induced disruption strengthens job insecurity and mental health problems - Kim, Taegoo Terry; Olorunsola, Victor O.; Karatepe, Osman M.; Lee, Yehah (Elsevier Sci Ltd, 2026)
We propose and test a multiple moderated mediation model that investigates the interrelationships of COVID-19 risk, psychological contract breach (PCB), job insecurity, rumination about job insecurity, and mental health problems. Data gathered from casino frontline employees was utilized to test said associations via PROCESS macro. The results revealed that COVID-19 risk exacerbated employees' mental health problems, while PCB strengthened the influence of COVID-19 risk on job insecurity. Rumination about job insecurity intensified the association between job insecurity and mental health problems. More importantly, PCB and rumination about job insecurity moderated the indirect positive impact of COVID-19 risk on mental health problems via job insecurity. This study enhances the understanding of how external threats, like COVID-19, combined with internal factors, engender mental health problems. These insights underscore the need for proactive mental health support and crisis management in high-stress environments.
Keywords: Casino frontline employees; COVID-19 risk; Job insecurity; Mental health problems; Psychological contract breach; Rumination about job insecurity; Dual moderated mediation model